Trinidad, School Children : No. 1 - Payne; Payne (Davidson and Todd Ltd [Printed in England], 2008)
Photograph of a group of black school children.
Colour:Green, blue and white hues ; Style:Landscape ; Other:Bordered, Divided
Keywords: Postcards; School children; Schoolboys; Schoolgirls